2015
DOI: 10.1111/hpb.12290
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status influences the likelihood but not the outcome of liver resection for colorectal liver metastasis

Abstract: Liver resection for CLM is performed more commonly among the least socioeconomically deprived population than among the most deprived. However, degree of deprivation was not associated with tumour recurrence after resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In agreement with previous studies, lower SES was associated with advanced stage at presentation 28,38 . It was also found that lower SES correlated with decreased receipt of MRI abdomen in colon patients, contrasting previous studies 39,40 . For example, Wiggans et al observed no significant difference in receipt of preoperative MRI abdomen in the most and least deprived groups of patients with colorectal liver metastases undergoing resection 40 .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In agreement with previous studies, lower SES was associated with advanced stage at presentation 28,38 . It was also found that lower SES correlated with decreased receipt of MRI abdomen in colon patients, contrasting previous studies 39,40 . For example, Wiggans et al observed no significant difference in receipt of preoperative MRI abdomen in the most and least deprived groups of patients with colorectal liver metastases undergoing resection 40 .…”
Section: Discussionsupporting
confidence: 81%
“…This was similarly found by Wiggans et al who identified that people in the least deprived SES categories accounted for a higher proportion of patients undergoing metastatic liver resection compared to the local population. 40 Similarly, those in the most deprived groups were less likely to receive the same intervention. 40 However, these disparities were not found to impact mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with CRC and a high socioeconomic status have more favourable surgical treatment characteristics than patients with a low socioeconomic status (99). Socioeconomic status also influences the likelihood of liver resection, where the socioeconomically favoured population are resected to a greater extent (100). In a large population-based series on surgical management and outcomes of patients with CRCLM, women, older patients and those who resided in the most socioeconomically deprived areas were significantly less likely to undergo surgical resection (101).…”
Section: Factors Influencing Surgical Resection Ratementioning
confidence: 99%